Awareness and perception of building maintenance practices among Apartment Seri Iskandar Residents / Muhammad Afiq Aiman Azmi and Amir Fasha Mohd Isa - Azmi, Muhammad Afiq Aiman; Mohd Isa, Amir Fasha (2023)
The thesis "Awareness and Perception of Building Maintenance Practices among Apartment Seri Iskandar Residents" delves into investigating the level of awareness and perception regarding building maintenance practices among residents of Apartment Seri Iskandar, a high-rise residential building in Malaysia. The study aims to assess the current state of building maintenance practices, understand residents' viewpoints on maintenance issues, and propose recommendations for enhancing maintenance management. The abstract provides an overview of the research background, problem statement, research aim, and objectives, emphasizing the significance of building maintenance in high-rise residential buildings and its relevance in addressing residents' maintenance challenges. It outlines the research methodology, including the literature review on building maintenance practices in Malaysia and the research design, encompassing both qualitative and quantitative methods like questionnaires, interviews, and secondary data analysis. By exploring residents' awareness and perception, the study aims to identify opportunities for enhancing building maintenance practices and ensuring the sustainability and safety of the apartment.